Banks cost efficiency, capital regulation, and risk taking in Africa a review and evaluation of patterns - Zunaidah, Sulong; Ibrahim, Traore (2017)
This review paper aims to examine and evaluate the current state and patterns of the relationship between bank cost efficiency, bank capital regulations, and bank risk taking by reviewing and assessing up to date published studies on this relationship in Africa. The linchpin of banks in the financial and economic system has been emphasized over times through financial deregulation, financial liberalization, financial integration, and most recently technology innovation and progress in financial intermediation. Financial intermediary like bank operates beyond their traditional functions. For instance, the bank has traditionally obtained funds from depositors, then lends those funds to borrowers (Gup, B. E. et al., 2007). That is bank bridges different interests between depositors and borrowers in term of liquidity and time preference of money Abdul, (2013). For banks to operate smoothly and efficiently, there must be a proper adjustment between banks' cost, capital, and risk for the long term survival, stability, and growth Bashir, A., & Hassan, A. (2017). However, the cyclical routine of banking crisis around the globe is a central debate among scholars and researchers. As cited in previous literatures, lack of a proper adjustment between banks cost efficiency, capital, and risk has been suggested as the main source of these panics Anderson, S. (2013). Thus, a proper selection of determinants of banks cost efficiency, capital regulation, and risk-taking, in order to measure the impacts of this relationship is the linchpin for long term survival, stability, and growth of any banking system in the world. This paper makes its contribution in several ways. First, there is an abundance of literature available in Europe, U.S., and Asia de Guevara, et al. (2007); Carbó, et al., (2009); Bashir, A., & Hassan, A. (2017), however, there is not much literature available in Africa that examines the relationship of Banks cost efficiency, capital regulation and risk taking in African. This study examines the empirical relationship between efficiency, risk and capital in the African banking sector. Second, this study includes the most recent banking data. This paper seeks to fill the gaps in literature by assessing and evaluating up to date published data solely on the relationship between cost efficiency, capital regulation, and risk taking in the African banking sector. The concluding remarks from this review is significant to academic research and policies, practices about the mentioned relationship. The findings of this study are also beneficial to the African central banks, African bank industry, researchers, policy and decision makers to assess the consequences of implementation in terms of capital regulation, risk reduction and efficiency enhancement.